PENGEMBANGAN FASILITAS DAN UTILITAS STASIUN BUMIAYU GUNA MENINGKATKAN PELAYANAN TERHADAP PENUMPANG - Suraharta, I Made; muhardjito, muhardjito; Mony, Rizky Farezi (Politeknik Perkeretaapian Indonesia Madiun, 2020)
The purpose of this study is to determine the condition of existing facilities at Bumiayu Station, to determine the factors that are the top priority of services at Bumiayu Station facilities and utilities to improve service quality. as well as planning the development of Bumiayu Station based on the results of an analysis of passenger satisfaction levels. This research is focused on developing existing facilities and utilities at Bumiayu station, and adjusted to the Minimum Service Standards (SPM) PM No. 63 of 2019. The facilities developed include: platforms, canopies (overcapping), parking lots and waiting rooms. And evaluating the service level of the station after and before the construction of data collection is carried out through a survey then the collected data is analyzed using the IPA (Importance Performance Analysis) method. The results of the Customer Statisfaction Index analysis show that passengers at Bumiayu Station at this time feel SATISFIED with the services provided with a value of 0.54. With the increase in the number of residents at Bumiayu Station each year, it is not certain that the following year passengers will be satisfied enough with the performance of passenger service at Bumiayu Station.